Power sector reforms and the poor : case study of Zambia - Simasiku, Mirriam (Energy Research Centre, 2014)
Power sector reforms around the world have been driven by various factors ranging from economic and financial to technological reasons. The reforms in the power sector are frequently undertaken under conditionality agreements linked to broader macro economic reforms. The main objective of this thesis is to find out whether power sector reforms advance social benefits to the poor, specifically increase their affordable access and use of electricity in Zambia. The rationale behind power sector reforms in Zambia include the increase of access to electricity by the majority of the Zambian population through expansion of the national electricity network to cover areas that have production potential. The promotion of private sector participation in the electricity industry by ensuring that market rules are attractive to private investors is another objective of reforms. The reforms also aim to improve efficiency in the electricity industry. To achieve the rationale of power sector reforms, the government's focus is on macro electrification projects. These electrification projects exclude poor household electrification owing to its unprofitable nature. Furthermore, the expected economic benefits arising from the macro electrification projects could result in further marginalization of poor household electrification. In short, the proposed approach to restructure the electricity industry in Zambia does not contain specific initiatives for increasing affordable access to electricity by the poor households. This thesis draws out the point that without considerable attention to affordable access to electricity by the poor at the inception of the reforms, addressing them at a later stage could difficult. To be effective, social concerns need to be included into the reform design early and backed by strong political commitment.